Karakteristik Morfometrik Sapi Aceh, Sapi PO dan Sapi Bali Berdasarkan Analisis Komponen Utama (AKU) - Mahmudi, Mahmudi; Priyanto, R.; Jakaria, Jakaria (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2019)
Aceh cattle  is one of four local cattle breeds (Aceh, Bali, Madura, and pesisir), and Ongole crossbreed is also regarded as the local cattle breed in Indonesia.  They are most likely to be well adapted to the environment, including disease, climate, feed and water availability. This study aims to determine the body size characteristics of Aceh, Bali, and Ongole crossbreed cattles. As many as 20 heads of Aceh, Bali, and Ongole crossbreed cattle respectively were used for measurement of 18 body parameters. Data obtained was then subkecyed to analysis of variance (ANOVA) and Principle Component Analysis (PCA). The results showed that morphometric measurements of Aceh, Ongole crossbreed, and Bali cattle were significantly different (P<0.05). PCA results showed that body measurement was detemined by chest circumference at Bali cattle, neck height at Ongole crossbreed, body length, and chest circumference at Aceh cattle. Meanwhile the shape components were chest widht at Ongole crossbreed and Bali cattle and thoracic part at Aceh cattle. This result should conribute to  phenotype profilinge of Bali cattle, Ongole crossbreed, and Aceh cattle, whic is important for cattle breeding and conservation in Indonesia.